Key enzymes involved in the utilization of fatty acids by Saccharomyces cerevisiae: a review - Wang, Zhaoyun; Su, Chunli; Zhang, Yisang; Shangguan, Sifan; Wang, Ruiming; Su, Jing (Frontiers in Microbiology, 2024)
Saccharomyces cerevisiae is a eukaryotic organism with a clear genetic background and mature gene operating system; in addition, it exhibits environmental tolerance. Therefore, S. cerevisiae is one of the most commonly used organisms for the synthesis of biological chemicals. The investigation of fatty acid catabolism in S. cerevisiae is crucial for the synthesis and accumulation of fatty acids and their derivatives, with β-oxidation being the predominant pathway responsible for fatty acid metabolism in this organism, occurring primarily within peroxisomes. The latest research has revealed distinct variations in β-oxidation among different fatty acids, primarily attributed to substrate preferences and disparities in the metabolic regulation of key enzymes involved in the S. cerevisiae fatty acid metabolic pathway. The synthesis of lipids, on the other hand, represents another crucial metabolic pathway for fatty acids. The present paper provides a comprehensive review of recent research on the key factors influencing the efficiency of fatty acid utilization, encompassing β-oxidation and lipid synthesis pathways. Additionally, we discuss various approaches for modifying β-oxidation to enhance the synthesis of fatty acids and their derivatives in S. cerevisiae, aiming to offer theoretical support and serve as a valuable reference for future studies.